Bringing a different approach to the problem of underdevelopment : A Turkish perspective - Köroğlu, Mustafa (My University, 2012)
Kalkınma; Türkiye Perspektifi; Azgelişmiş Ülkeler; Küreselleşme ÖZET AZGELİŞMİŞLİK PROBLEMİNE FARKLI BİR YAKLAŞIM GETİRMEK: TÜRKİYE PERSPEKTİFİ Kalkınma ekonomisi, 1950’lerde ortaya çıkışından beri zaman içinde insani eksenli görüşleri kapsayarak gelişmiştir. Küreselleşme çağında, modern kalkınma araştırmaları çok boyutlu bir anlayışı içinde barındırmaktadır. Son küresel kriz sonrasında, UNCTAD’ın Yeni Uluslararası Kalkınma Mimarisi (NIDA) yaklaşımı, uluslararası toplumun azgelişmişliğe yönelik bütüncül bir bakış elde etmesinde önemli bir adımı oluşturmaktadır. Bu çalışmalar azgelişmiş ülkelerin kronik problemlerinin takip eden yıllarda nasıl ele alınacağına katkıda bulunmaktadır. Bu çalışmanın ana hedefi kalkınma iklimindeki değişim ve azgelişmiş ülkelere yönelik artan küresel kalkınma çalışmaları ışığında Türkiye’nin azgelişmişlik perspektifini elde etmektir. Türkiye’nin uluslararası kalkınma yardımlarına yönelik yapılan önceki çalışmalardan farklı olarak, bu çalışma sivil toplum örgütleri ile devlet kalkınma kurumlarını beraber inceleyerek Türkiye’nin azgelişmiş ülkelere yönelik kapsamlı yaklaşımını elde etmeyi amaçlamaktadır. Ayrıca, insani yardım dernekleri, işadamları örgütleri, Türk İşbirliği ve Koordinasyon Ajansı Başkanlığı, Türk Kızılay derneği ve Türk okulunun faaliyetleri göz önüne alınarak, Türkiye’nin azgelişmişlik vizyonunun Batılı kurumlardan farklı olup olmadığını değerlendirmeyi amaçlamaktadır. Development; Turkish Perspective; Underdeveloped Countries; Globalization

BRINGING A DIFFERENT APPROACH TO THE PROBLEM OF UNDERDEVELOPMENT: A TURKISH PERSPECTIVE Development economics has been in progress since its emergence in the 1950s which has incorporated human-related concepts in time. In the age of globalization, the contemporary discourse of development has embraced a multi-dimensional understanding. After the post-global crisis, the approach of New International Development Architecture (NIDA) to the UNCTAD constitutes a vital step for the international community to acquire an integrated view on underdevelopment. These efforts contribute to how the chronic problems of the underdeveloped countries will be handled in the subsequent years. The main objective of this thesis is to obtain Turkish perspective on underdevelopment in light of the evolution of development climate and increasing global development efforts for underdeveloped countries. Being different from previous studies on Turkish international development assistance, this thesis aims to obtain a comprehensive approach of Turkey to the underdeveloped countries by examining non-governmental organizations together with state development agencies. In regard to the activities of these organizations, including those of humanitarian aid organizations, businessmen associations, Turkish International Cooperation and Coordination Agency (TİKA), Turkish Red Crescent Society and Turkish school, it is also aimed to assess whether the vision of Turkey on underdevelopment is different from that of Western organizations.
Keywords: Az Gelişmiş Ülkeler; Kalkınma; Küreselleşme